(untitled) (Journal of Humanities and Social Sciences Research, 2023)
and learn free swimming for beginners, and to identify the effect of the educational program with water games to develop some motor abilities and learn free swimming for beginners. The researchers used the experimental method in the manner of the two (equivalent) groups, the experimental and the control equally, due to its suitability to the nature of the problem. The research sample (24) beginners were divided into two groups, so the number of the experimental group was (12) beginners and the same number of the control group (12) beginners, and after completing the testing and measurement process for the research variables for the pre and post tests, and then applying the research experiment, the results were reached as follows: 1-There are statistically significant differences in favor of the educational program in developing the motor abilities under study. 2-There are statistically significant differences in favor of the educational program in developing the performance of freestyle swimming for beginners? The researchers recommend the following: 1-Adopting the educational water sports program to teach different levels in the free swimming event. 2-Using modern means and tools to learn freestyle swimming for beginners